PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN PADA INDOMARET DI KECAMATAN GARUT KOTA - Ramayani Yusuf; Libia (Jurnal Manajemen dan Pemasaran, 2024)
The purpose of this study was to determine whether there is a significant influence between service quality and customer satisfaction at Indomaret in Garut City District. This type of research uses quantitative research with a sample size of 100 customers or visitors to Indomaret in Garut City sub-district. The data collection method in this study is to use the associative method, which aims to find the relationship between two or more variables. The data obtained was analyzed using a data analysis tool, namely SPSS with a simple linear regression analysis test. The results of the data analysis show that service quality has a significant and positive effect on customer satisfaction at Indomaret in Garut Kota sub-district.